How IT Governance can assist IoT project implementation - Henriques, David (2021)
Internet of things (IoT) is considered a key technology for the Industry 4.0 revolution. Information Technology (IT) governance (ITG) is now an increasingly important tool for organizations to align their IT strategy and infrastructures with the organizations’ business objectives. The most adopted ITG framework is COBIT, which defines seven enabler categories. These enablers aim to facilitate the implementation, identification, and management of IT. This research aims to determine, explore, and define which are the most suitable IT governance enablers to assist managers in IoT implementation. The study adopted the Design Science Research methodology, including two systematic literature reviews and a Delphi method to build the artefact. The artefact was demonstrated and evaluated in a real organization. The results indicate that data privacy, data protection, and data analysis are currently the most relevant enablers to consider in an IoT implementation because they increase the efficiency of the solution and enhance data credibility.